EVALUATING THE COMPETENCY OF ELEVENTH-GRADE STUDENTS OF VOCATIONAL SCHOOL IN CRAFTING AUTOBIOGRAPHICAL TEXTS - Saputra, Benny; Dewi, Desi Surlitasari (English Department, University of Riau Kepulauan, Batam,Indonesia, 2024)
This study evaluates the writing skills of eleventh-grade students at SMK Hang Nadim Batam in composing autobiographical texts. Autobiography, which involves writing about one’s own life, is a key component of the curriculum for vocational high school students. The primary aim of this study is to assess the proficiency of these students in writing autobiographies. Employing a descriptive qualitative research approach, this study analyzes student writing to provide a detailed description of their skills. The analysis includes examining the organization, content logic, grammar (including the use of simple present, past, and future tenses), mechanics (legibility and neatness), and vocabulary (word choice). The findings indicate that students demonstrated a competent level of writing skills. Specifically, their autobiographical texts generally exhibited well-organized content, logical sequencing, appropriate tense usage, and adequate vocabulary. However, there are areas for improvement. The study offers recommendations for teachers, students, and future researchers, suggesting that these findings could serve as a reference for enhancing English instruction and guiding further research in this area.